The Role of Attitude in Mediating Environmental Knowledge and Eco-Friendly Food Purchase Intention - Widanti, Afrima; Anggri Puspita Sari; Seprianti Eka Putri (UNIB Press, 2026)
This study examines the influence of environmental knowledge on consumers’ purchase intention toward eco-friendly food, both directly and indirectly through attitude as a mediating variable. Although public awareness of environmental issues continues to increase, this awareness has not been consistently translated into sustainable consumption behavior, particularly in the food sector. This discrepancy underscores the need to examine the psychological mechanisms underlying green purchase intentions. A quantitative research design was employed using Partial Least Squares-SEM (PLS-SEM) with SmartPLS 3.0. The study population comprised Indonesian consumers who were familiar with eco-friendly food products. Data were collected through an online questionnaire disseminated via social media platforms between July and September 2025. Of the 161 responses obtained, 137 questionnaires met the criteria for further analysis. The findings reveal that environmental knowledge has a positive and significant effect on both attitude and purchase intention toward eco-friendly food. In addition, attitude demonstrates a significant positive influence on purchase intention. Importantly, attitude partially mediates the relationship between environmental knowledge and purchase intention, indicating that knowledge alone is insufficient to fully drive consumers’ purchase intentions in the absence of favorable attitudes. These results lend empirical support to the Theory of Planned Behavior, highlighting the pivotal role of attitude in translating environmental knowledge into intentional purchasing behavior. This study advances the consumer behavior literature on green consumption and offers practical insights for businesses and policymakers to strengthen environmental education initiatives and cultivate positive consumer attitudes toward eco-friendly food.